Burnout syndrome – a serious danger in modern societies / Sindrom izgorelosti – resna nevarnost sodobne družbe - Pahor, Dušica (Acta Medico-Biotechnica, 2021)
We often hear people say that they are tired, exhausted, and unable to carry on in their private, as well as their professional lives. Sadly, this has become the accepted norm and is considered part of modern society; where exhaustion and fatigue have their places alongside mobile phones and computers. Have we accepted and become resigned to this situation?